PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SEBAGAI UPAYA MENINGKATKAN KEPUASAN DAN LOYALITAS PELANGGAN PADA GELORA MUKTI SPORT BERBASIS WEB - Anang Supriatna; Heru Budianto (FKOM UNIKU, 2019)
Gelora Mukti Sport still uses a conventional system in managing its products and customers. Conventional system causes inaccuracies in managing data item data, inventory and customer data. Increasig loyalty is done by providing good service. This study aims to increase consumer loyalty through the application of CRM. This study uses waterfall as method of developing system. The stages of the waterfall are analyzing system requirements, making system design, implementing systems, testing and operating and maintaining the system. The form of implementation of CRM applied at Gelora Mukti Sport is by giving discounts on certain days, giving points provided that they will get 10 points for one transaction, points with a certain amount can be exchanged for products or vouchers that have been provided, vouchers can be used to deduct the total amount of payment, and wallet is useful for payment of product orders where the wallet is obtained from refunds and means of criticism to provide criticism or suggestions for the Gelora Mukti Sport store. The application of CRM in this system is expected to be able to improve service so that it impacts on the increase of consumer loyalty.Keyword : Gelora Mukti Sport, operational CRM, Waterfall, loyalty, discounts, vouchers, wallet, web, customers